Relationship between the ability to change from a supine to a sitting position at admission and mobility outcomes after stroke rehabilitation - Wattanapan,P. (Medical Association of Thailand, 2015)
Background: Regarding observations, stroke patients able to change their basic body position from supine to sitting at admission usually could walk by the end of rehabilitation. However, there was not yet supported by any research evidence. Objective: To study the relationship between the patient's ability at admission to change basic body position from a supine to a sitting position and the mobility outcome after stroke rehabilitation. Material and Method: Data were gathered and analyzed from the case record forms (including the Barthel ADL Index assessment sheets) of 327 stroke patients in nine tertiary in-patient rehabilitation settings in Thailand between March and December 2006. Results: On admission, 58.7% of the patients were able to change their basic position from supine to sitting. At the end of rehabilitation, the group which was able to sit had a higher mobility sub-score (OR = 6.15; 95% CI 3.24 -11.67) and total Barthel ADL index score (OR = 9.64; 95% CI 5.74-16.18) than the group which was unable to sit. Conclusion: The ability at admission to change from a supine to a sitting position was significantly related to a better mobility outcome after stroke rehabilitation.